Analisis kemampuan berpikir kritis peserta didik ditinjau dari self-confidence - Nugraha, Khansa Zalikha; Widiati, Indah (Mahesa Research Center, 2023)
Students' critical thinking abilities which are still low need to be developed and one of the abilities that must be instilled in students is self-confidence. This research aims to describe students' mathematical critical thinking abilities in terms of self-confidence. The type of research used in this research is qualitative research with a case study method. The research subjects were 9th-grade students at one of the junior high schools in Siak Hulu and numbered 33 people. The data collection technique in this research is a test technique using mathematical critical thinking ability test instruments and non-test techniques in the form of student self-confidence questionnaires and interviews. The data analysis technique is carried out through several stages, including reducing data, presenting data, and drawing conclusions. Based on the research results, it was found that; (1) overall students' mathematical critical thinking abilities are classified as less critical and need to be improved; (2) self-confidence is in line with mathematical critical thinking skills where students with high self-confidence have sufficient critical thinking skills which are indicated by students being able to master two indicators of critical thinking. Students with moderate self-confidence have sufficient critical thinking skills, which is indicated by students being able to master two critical thinking indicators. In contrast, students with low self-confidence have sufficient critical thinking skills, which is indicated by students being able to master two critical thinking indicators.